Enhancing the Professionalism of Muslim Journalists in Handling Disinformation and Hoaxes During the COVID-19 Pandemic - Satriani, Arba'iyah; Permatasari, Andalusia Neneng; Firmansyah, Firmansyah (ASEAN Journal of Community Engagement, 2022)
The term alternative media refers to media that serves as alternative sources of information in lieu of mainstream media. In contrast to social media, alternative media are mass media entities that carry out journalistic functions even though they are affiliated with community organizations. Thus, alternative media are expected to provide authentic news just like mainstream media in Muslim countries. Islamic alternative media are also required to produce quality news, and this was especially seen during the COVID-19 pandemic, when a flood of information resulted in confusion among the community. In response, training that aimed to enhance journalistic professionalism for practitioners of Islamic alternative journalism from four alternative media entities was conducted during the pandemic. Entitled Enhancing Professionalism of Muslim Journalists, the training was carried out in a measurable manner using the Assets-Based Community Development (ABCD) approach, which consists of five steps, namely discovery, dream, design, define, and destiny. With these five steps, the training resulted in significant changes in how journalist carried out their jobs. These include improvements in their understanding of professional ethics, news writing, and the use of journalistic language. This training also provided an overview of the pattern of reporting in Islamic alternative media, which are platforms that can provide news from a religious perspective.